Radio broadcasting in the era of HIV/AIDS: Can this be the magic bullet? - Nyawasha, Tawanda Sydesky; Chipunza, Crispen (Sage: International Social Work, 2015)
In this study, we assessed the relevance and effectiveness of radio broadcasting as a strategy that facilitates the adoption and use of safer sexual practices among students at a South African university. Based on ethnographic data, the article highlights that the essential and critical contribution of campus radio lies in its ability to create a social space for HIV/AIDS communication. The overall aim of this study was to assess the relationship between exposure to radio broadcasting messages and the adoption of safer sexual practices. Our analysis suggests that campus broadcasting can be instrumental in promoting HIV/AIDS awareness and education.
Published Article
Keywords: Behaviour change; critical awareness; HIV/AIDS communication; mass media; social space